2003
DOI: 10.1007/s00345-003-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and male fertility

Abstract: Androgens play a crucial role in the development of male reproductive organs such as the epididymis, vas deferens, seminal vesicle, prostate and the penis. Furthermore, androgens are needed for puberty, male fertility and male sexual function. High levels of intratesticular testosterone, secreted by the leydig cells, are necessary for spermatogenesis. Intratesticular testosterone is mainly bound to androgen binding protein and secreted into the seminiferous tubules. Inside the sertoli cells, testosterone is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
192
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(212 citation statements)
references
References 25 publications
8
192
0
12
Order By: Relevance
“…Interestingly, it is notable that heavy exercise does not appear to have significantly altered the percentage of the tapered head. Torres-Colleja et al studied the effect of AAS in 30 adult male bodybuilders, 6 who reported that sperm count, percentage of normal sperm morphology and FSH level were significantly reduced, this results agree with our results, on the other hand they found that the LH level didn't vary in the same group. This finding disagrees with our result (LH level significantly reduced in exercise and treated group) may be due to the different doses of AAS taken by bodybuilders.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, it is notable that heavy exercise does not appear to have significantly altered the percentage of the tapered head. Torres-Colleja et al studied the effect of AAS in 30 adult male bodybuilders, 6 who reported that sperm count, percentage of normal sperm morphology and FSH level were significantly reduced, this results agree with our results, on the other hand they found that the LH level didn't vary in the same group. This finding disagrees with our result (LH level significantly reduced in exercise and treated group) may be due to the different doses of AAS taken by bodybuilders.…”
Section: Discussionsupporting
confidence: 92%
“…6 In addition, numerous studies have shown that severe depletion of Leydig cells following treatment by AAS, 7 Leydig cells are known to have receptors for LH that stimulates these cells to produce testosterone. 8 On the other hand, exercise training frequently results in a decrease of serum testosterone, and may rarely be associated with reduced libido, sperm production, and fertility.…”
mentioning
confidence: 99%
“…Testosterone is the principal hormone ensuring normal spermatogenesis and inhibition of germ cell apoptosis (Dohle et al 2003). In the present study, a gradual decrease in serum testosterone level was determined in the lindane-treated groups and this hormonal disturbance was associated with the interstitial cell degeneration.…”
Section: Discussionmentioning
confidence: 57%
“…Androgens specifically testosterone with high levels are necessary for active spermatogenesis. [36] The efficiency of spermatogenesis and fertility are increased in males as a result of synergistic effect of FSH and testosterone whereas LH stimulates spermatogenesis through stimulating testosterone production in Leydig cells. It has been considered that low levels of FSH and LH prevent gonads from either producing sperms or insufficient amount of testosterone production.…”
Section: Antispermatogenic Activitymentioning
confidence: 99%